The ETF Community of Innovative Educators: reflections after four years of collaborative learning - Nascimbeni, Fabio (Proceedings of the International Conference on Networked Learning, 2026)
The paper presents some reflections on how to support community and network-based learning dynamics among educators, as emerging from the work of the Community of Innovative Educators of the European Training Foundation. In its four years of life, the community has reached over 1600 registered members, organised 48 interactive webinars on different aspects of teaching innovation, collected 127 blogpost and 124 innovative teaching and learning practices, and has fostered the involvement of its members in the co-production of tools to support teaching innovation. We critically reflect on the most important strategies to make sure that within such communities participation transforms into engagement, and engagement produces learning, despite all the constrains and difference that are typical of such communities. We analyse how shared goals, interactivity, diversity, flexible support, awarding mechanisms, and co-creation dynamics contribute to a healthy and growing learning community.